Oral mucosa reconstruction methods in cancer patients - M. A. Ilina; S. A. Kravtsov (Опухоли головы и шеи)
Resection of malignant neoplasms of the oral cavity causes esthetic, functional, and anatomical defects irrespective of the advancement of tumor process. The methods of oral cavity organ reconstruction include the use of distant flaps and microsurgical autotransplantation. microsurgical techniques have limits and are not always applicable in clinical practice.The article presents the main techniques of oral cavity organ reconstruction alternative to microsurgical techniques. Detailed literature review on this topic is performed, advantages and disadvantages of the various methods of defect reconstruction are presented. In clinical practice, the use of distant flaps is an adequate alternative to microsurgical autotransplantation. This method can be successfully used in weakened patients with locally advanced squamous cell carcinoma of the oral mucosa.